2013
DOI: 10.3844/ajavsp.2013.230.238
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Epidural Dexmedetomidine, Ketamine or Fentanyl in Combination With Bupivacaine in Dogs

Abstract: Castration is one of the most common procedure. It is a potential source of mild to moderate pain which is enough to induce inflammatory process, necessitate the incorporation of analgesics. This study was designed to evaluate the effect of epidural bupivacaine alone or in association with fentanyl, ketamine or dexmedetomidine on analgesia for the first 24 h post surgical castration. Forty male mongrel dogs were randomly allocated into 4 groups received bupivacaine 0.25% (1.5 mg kg ) into the lumbosacral space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Kang reported that dexmedetomidine administration during surgery reduced the intraoperative and postoperative secretion of cytokines, including the proinflammatory cytokines tumor necrosis factor-a, interleukin-1b and IL-6, and the antiinflammatory cytokines IL-4 and CRP (Kang et al, 2013). Nour EM also found that epidural administration of dexmedetomidine as an adjunct to bupivacaine inhibited the increase in plasma IL-6 (Nour et al, 2013). Similarly, in this study, the postoperative IL-6 and CRP levels in the RD 3 group and RD 5 group were lower than those in the R group after FIGURE 6 | Heart rate among the three groups.…”
Section: Discussionmentioning
confidence: 97%
“…Kang reported that dexmedetomidine administration during surgery reduced the intraoperative and postoperative secretion of cytokines, including the proinflammatory cytokines tumor necrosis factor-a, interleukin-1b and IL-6, and the antiinflammatory cytokines IL-4 and CRP (Kang et al, 2013). Nour EM also found that epidural administration of dexmedetomidine as an adjunct to bupivacaine inhibited the increase in plasma IL-6 (Nour et al, 2013). Similarly, in this study, the postoperative IL-6 and CRP levels in the RD 3 group and RD 5 group were lower than those in the R group after FIGURE 6 | Heart rate among the three groups.…”
Section: Discussionmentioning
confidence: 97%
“…Kang et al reported that dexmedetomidine administration during surgery reduced intraoperative and post-operative secretion of cytokines, including the pro-inflammatory cytokines tumour necrosis factor-α, interleukin-1β and IL-6 and anti-inflammatory cytokines IL-4 and CRP level in their study [ 26 ]. Nour EM et al also found that epidural administration of dexmedetomidine adjunct to bupivacaine inhibited the increment of plasma interleukin-6 [ 27 ]. Similarly, in this study the postoperative IL-6 level was lower in Bup+Dex(3) and Bup+Dex(5) groups than Bup group in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] The aim of the addition of adjuvant drugs to 0.5% bupivacaine is one of the goals of anesthesiologists in the management of patients with lower limb fracture, especially femoral fracture, in order to control postoperative pain and increase patient satisfaction. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%